Rapid and Simultaneous Detection of Vibrio parahaemolyticus, Salmonella spp. and Escherichia coli in Fish by Multiplex PCR - Radestya Triwibowo; Novalia Rachmawati; Dwiyitno Dwiyitno (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2020)
Pathogenic bacteria are commonly found as natural contaminants in seafood and fish products. Globally, several countries have been imposing strict regulations on the maximum levels of pathogens and consequently require microbial testing of pathogens before the products can be marketed. A culture-based method with biochemical assay has been widely used to detect pathogenic bacteria in food, despite its long and extensive process. Meanwhile, the alternative molecular-based method to overcome this problem, cannot differentiate between viable and nonviable cells, which may lead to underestimation. This study aimed to develop a multiplex PCR (mPCR) method as a confirmatory assay for the culture-based method to detect pathogens in fish products simultaneously. This method applied a pre-enrichment step to ensure the growth of low-level pathogens and the injured cells in the sample. The target genes were ToxR, InvA, and UidA for Vibrio parahaemolyticus, Salmonella spp. and Escherichia coli, respectively. This assay also amplified the 16S rDNA gene of bacteria as an internal control for the PCR reaction. By implementing liquid-based DNA extraction during analysis, the developed-mPCR was comparable to detect the targeted bacteria in artificially-contaminated samples. The method was more sensitive in naturally-contaminated samples, where the number of E. coli, Salmonella spp. and V. parahaemolyticus detected were 28, 7, and 22, respectively. While the conventional method only detected 26, 5, and 19 of the respective pathogens. With a relatively shorter time and lower operation cost, the mPCR method is potential as an alternative for the culture-based method.